Assay methods based on proximity-enhanced reactions for detecting non-nucleic acid molecules - Park, Ye Seop; Choi, Sunjoo; Jang, Hee Ju; Yoo, Tae Hyeon (Frontiers in Bioengineering and Biotechnology, 2023)
Accurate and reliable detection of biological molecules such as nucleic acids, proteins, and small molecules is essential for the diagnosis and treatment of diseases. While simple homogeneous assays have been developed and are widely used for detecting nucleic acids, non-nucleic acid molecules such as proteins and small molecules are usually analyzed using methods that require time-consuming procedures and highly trained personnel. Recently, methods using proximity-enhanced reactions (PERs) have been developed for detecting non-nucleic acids. These reactions can be conducted in a homogeneous liquid phase via a single-step procedure. Herein, we review three assays based on PERs for the detection of non-nucleic acid molecules: proximity ligation assay, proximity extension assay, and proximity proteolysis assay.
Keywords: Acid molecules; Assay methods; Biological molecule; Protein molecules; Proximity extension assay; Proximity ligation assay; Proximity proteolysis assay; Proximity-enhanced reaction; Reliable detection; Small molecules; biosensor; proximity extension assay; proximity ligation assay; proximity proteolysis assay; proximity-enhanced reaction